Precise assignment of the heavy-strand promoter of mouse mitochondrial DNA: cognate start sites are not required for transcriptional initiation. - Chang, D D (1986)
Transcription of the heavy strand of mouse mitochondrial DNA starts from two closely spaced, distinct sites located in the displacement loop region of the genome. We report here an analysis of regulatory sequences required for faithful transcription from these two sites. Data obtained from in vitro assays demonstrated that a 51-base-pair region, encompassing nucleotides -40 to +11 of the downstream start site, contains sufficient information for accurate transcription from both start sites. Deletion of the 3' flanking sequences, including one or both start sites to -17, resulted in the initiation of transcription by the mitochondrial RNA polymerase from alternative sites within vector DNA sequences. This feature places the mouse heavy-strand promoter uniquely among other known mitochondrial promoters, all of which absolutely require cognate start sites for transcription. Comparison of the heavy-strand promoter with those of other vertebrate mitochondrial DNAs revealed a remarkably high rate of sequence divergence among species.